Forgotten Voices of the Great War - Arthur, Max (London Ebury Press, 2003)
A team of academics, archivists and volunteers set about tracing First World War veterans and interviewing them in order to record the experiences of ordinary individuals in war.
Include Illustrations and Index
Keywords: Oral history -- World War (1914-1918)